Chromosomal-level genome assembly of Melastoma candidum provides insights into trichome evolution - Zhong, Yan; Wu, Wei; Sun, Chenyu; Zou, Peishan; Liu, Ying; Dai, Seping; Zhou, Renchao (Frontiers in Plant Science, 2023)
Melastoma, consisting of ~100 species diversified in tropical Asia and Oceania in the past 1-2 million years, represents an excellent example of rapid speciation in flowering plants. Trichomes on hypanthia, twigs and leaves vary markedly among species of this genus and are the most important diagnostic traits for species identification. These traits also play critical roles in contributing to differential adaptation of these species to their own habitats. Here we sequenced the genome of M. candidum, a common, erect-growing species from southern China, with the aim to provide genomic insights into trichome evolution in this genus. We generated a high-quality, chromosome-level genome assembly of M. candidum, with the genome size of 256.2 Mb and protein-coding gene number of 40,938. The gene families specific to, and significantly expanded in Melastoma are enriched for GO terms related to trichome initiation and differentiation. We provide evidence that Melastoma and its sister genus Osbeckia have undergone two whole genome duplications (WGDs) after the triplication event (γ) shared by all core eudicots. Preferential retention of trichome development-related transcription factor genes such as C2H2, bHLH, HD-ZIP, WRKY, and MYB after both WGDs might provide raw materials for trichome evolution and thus contribute to rapid species diversification in Melastoma. Our study provides candidate transcription factor genes related to trichome evolution in Melastoma, which can be used to evolutionary and functional studies of trichome diversification among species of this genus.